2018
DOI: 10.1016/j.joca.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between knee joint contact forces and external knee joint moments in patients with medial knee osteoarthritis: effects of gait modifications

Abstract: At the first peak, KAM is a reasonable substitute for the medial contact force, but not at the second peak. First peak KFM is also a significant contributor to the medial KCF. At the first peak, walking with a modified gait reduced the ratio of the medial to total KCF but not the medial KCF itself. To determine the effects of gait modifications on cartilage loading and disease progression, longitudinal studies and individualized modeling, accounting for motion control, would be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 50 publications
2
97
0
1
Order By: Relevance
“…The second peak value of the KAM, as shown in Figure 5, is higher than the first peak which is inconsistent with those in the literature during the natural and toe-in gaits. It might be due to variations in the placement of markers and because healthy individuals were measured in this paper while other studies measured subjects with OA or TKA [14,17,35]. However, the results in Figures 4 and 6 showed that the toe-in and toe-out gaits had little effects on the GRFs and TF joint contact forces (p > 0.05) but that it has significant influence on the KAM and KFM during the stance phase (p < 0.05), as shown in Figure 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The second peak value of the KAM, as shown in Figure 5, is higher than the first peak which is inconsistent with those in the literature during the natural and toe-in gaits. It might be due to variations in the placement of markers and because healthy individuals were measured in this paper while other studies measured subjects with OA or TKA [14,17,35]. However, the results in Figures 4 and 6 showed that the toe-in and toe-out gaits had little effects on the GRFs and TF joint contact forces (p > 0.05) but that it has significant influence on the KAM and KFM during the stance phase (p < 0.05), as shown in Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Trunk lean is reported to be highly efficient in reducing peak KAM values, while potential adverse effects including lower back discomfort, imbalance, and difficulty in maintenance for a long time [12,13]. Although the toe-in and toe-out gait patterns could alleviate the progression of knee OA (osteoarthritis), the detailed mechanism is still vague [14,15]. Gait modification has showed positive benefits at the knee joint, but it might be associated with negative effects on other joints; the longer-term effects of the toe-in and toe-out gait modifications in patients with knee OA is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Поэтому наиболее частой локализацией заболевания является один из самых нагружаемых суставов -коленный (КС). ОА КС является одной из наиболее распространенных причин инвалидности в мире (20-40% у лиц старше 75 лет) [1,2]. Эндопротезирование (ЭП) КС оказалось экономически эффективным и надежным методом лечения ОА КС, что делает его одним из самых распространенных оперативных вмешательств на суставах, выполняемых ежегодно, с прогнозируемым увеличением спроса [3][4][5].…”
Section: Changes In Gait Parameters During Rehabilitation After Totalunclassified